The aesthetic of Johann Sebastian Bach - Pirro, André 1869-1943 (Rowman & Littlefield, 2014)
"Pirro's work is based primarily on an examination of the close relationships between language and music in Bach's vocal works and provides us with an extensive and well-researched "lexicon" of the expressive resources of Bach and his contemporaries. Pirro's study thus serves as a still sound basis for understanding and interpreting Bach's instrumental works"...Provided by publisher